2010
DOI: 10.1124/jpet.110.173260
|View full text |Cite
|
Sign up to set email alerts
|

N-Substituted Benztropine Analogs: Selective Dopamine Transporter Ligands with a Fast Onset of Action and Minimal Cocaine-Like Behavioral Effects

Abstract: Previous studies suggested that differences between the behavioral effects of cocaine and analogs of benztropine were related to the relatively slow onset of action of the latter compounds. Several N-substituted benztropine analogs with a relatively fast onset of effects were studied to assess whether a fast onset of effects would render the effects more similar to those of cocaine. Only one of the compounds increased locomotor activity, and the increases were modest compared with those of 10 to 20 mg/kg cocai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 36 publications
6
42
0
Order By: Relevance
“…Likewise, muscarinic M 2 sites seem improbable, as the BZT-derived atypical DAT inhibitors have a wide variety of reported activity at this site. Notably, the N-substituted BZT analog GA-299 had little cocaine-like activity and lacked affinity for the M 2 muscarinic site (Li et al, 2011). Previous studies have also found inconsistencies in affinities at 5-HT 1 binding sites among N-substituted BZT analogs Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, muscarinic M 2 sites seem improbable, as the BZT-derived atypical DAT inhibitors have a wide variety of reported activity at this site. Notably, the N-substituted BZT analog GA-299 had little cocaine-like activity and lacked affinity for the M 2 muscarinic site (Li et al, 2011). Previous studies have also found inconsistencies in affinities at 5-HT 1 binding sites among N-substituted BZT analogs Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the D 3 R affinity of LX-20, which did not stimulate locomotor activity, was greater than that for LX-19, which did stimulate activity, and greater than its affinity for the DAT, suggesting a role for D 3 Rs in the atypical effects of LX-20. However, Li et al (2011) examined a group of BZT analogs that were considered atypical DAT ligands. Within that group, the compound that was most like cocaine, JHW013, had the greatest affinity for D 3 Rs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-documented that cocaine's rapid onset of action contributes to its highly-rewarding efficacy and addictive potential (Busto and Sellers, 1986;Kimmel et al, 2008;Kimmel et al, 2007), although not all studies support this view (Li et al, 2011). In rodents, different rates of cocaine delivery affect its addictive liability-drugs reaching the brain rapidly are more addictive than those that reach the brain slowly (Oldendorf, 1992;Samaha and Robinson, 2005;Wakabayashi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the slower association rates with DAT might result in a cocaine-antagonist action. However, a study introduced several atypical dopamine uptake inhibitors with fast association rates with DAT in mice [17]. Therefore, it appears that the slower association rates with DAT are not essential for induction of a cocaine-antagonist action, either.…”
Section: Differences In Kinetic Variablesmentioning
confidence: 99%